1996
DOI: 10.1172/jci118842
|View full text |Cite
|
Sign up to set email alerts
|

Different clinical behaviors of acute hepatitis C virus infection are associated with different vigor of the anti-viral cell-mediated immune response.

Abstract: The anti-viral T cell response is believed to play a central role in the pathogenesis of hepatitis C virus infection. Since chronic evolution occurs in Ͼ 50% of HCV infections, the sequential analysis of the T cell response from the early clinical stages of disease may contribute to define the features of the T cell response associated with recovery or chronic viral persistence. For this purpose, 21 subjects with acute hepatitis C virus infection were sequentially followed for an average time of 44 wk. Twelve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
463
2
7

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 636 publications
(495 citation statements)
references
References 21 publications
(25 reference statements)
23
463
2
7
Order By: Relevance
“…Although these do appear to be targeted, this is not exclusive and responses to other gene products are also seen [17]. The strength of the CD8 + T cell response against one epitope when measured using a tetramer, may be up to 8% of the total CD8 + T cells, and can include responses to at least 8 separate epitopes [10].…”
Section: Cellular Immunology Of Hcvmentioning
confidence: 99%
“…Although these do appear to be targeted, this is not exclusive and responses to other gene products are also seen [17]. The strength of the CD8 + T cell response against one epitope when measured using a tetramer, may be up to 8% of the total CD8 + T cells, and can include responses to at least 8 separate epitopes [10].…”
Section: Cellular Immunology Of Hcvmentioning
confidence: 99%
“…While HCV is spontaneously cleared with a vigorous and broad virus-specific effector T-cell response, such responses are impaired in persistent infections (1)(2)(3)(4)(5). While most studies have focused on the antiviral effector cytokine IFNγ, a role for the immune regulatory cytokine interleukin-10 (IL-10) has been suggested by enhanced HCV titers and reduced hepatic fibrosis during exogenous IL-10 therapy in HCV-infected patients (6) as well as associations between IL-10 promoter polymorphisms and clinical outcomes (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Natural history studies have found that 15%-59% of people who are infected with HCV will undergo spontaneous viral clearance with no further liver disease due to HCV [3][4][5][6][7][8][9][10][11] . The remaining will develop chronic HCV infection that can lead to cirrhosis, hepatocellular carcinoma and the need for a liver transplant.The exact mechanism of HCV RNA clearance is not well understood although recent studies have shown that clearance is associated with strong, broad cellular immune responses [12][13][14][15][16][17][18][19] . Other factors such as younger age [3,20] , female gender [21,22] , presence of hepatitis B surface antigen (HBsAg) [3,23] , certain HLA alleles [6,[24][25][26][27][28][29] , and low viral quasispecies diversity [30] have been linked to increased HCV RNA clearance.…”
mentioning
confidence: 99%